2013
DOI: 10.1016/j.foodres.2012.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Screening of lactic acid bacteria isolated from fermented table olives with probiotic potential

Abstract: You may download, copy and otherwise use the AAM for non-commercial purposes provided that your license is limited by the following restrictions:(1) You may use this AAM for non-commercial purposes only under the terms of the CC-BY-NC-ND license.(2) The integrity of the work and identification of the author, copyright owner, and publisher must be preserved in any copy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
145
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(153 citation statements)
references
References 38 publications
7
145
0
1
Order By: Relevance
“…Furthermore, the principal component analysis (PCA) was employed to investigate relationships among samples. The input matrix used for HCA and PCA consisted of the total area under growth/decline curves of LAB, yeasts, enterobacteria, pseudomonads, CPS, as well as pH values (Bautista-Gallego et al, 2011;Blana et al, 2014). Areas were calculated by integration using the OriginPro 7.5 software (OriginLab Corporation, Northampton, USA).…”
Section: Statistical and Explorative Multivariate Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the principal component analysis (PCA) was employed to investigate relationships among samples. The input matrix used for HCA and PCA consisted of the total area under growth/decline curves of LAB, yeasts, enterobacteria, pseudomonads, CPS, as well as pH values (Bautista-Gallego et al, 2011;Blana et al, 2014). Areas were calculated by integration using the OriginPro 7.5 software (OriginLab Corporation, Northampton, USA).…”
Section: Statistical and Explorative Multivariate Analysismentioning
confidence: 99%
“…Areas were calculated by integration using the OriginPro 7.5 software (OriginLab Corporation, Northampton, USA). In addition, other relevant indexes of pH and microbial changes were taken into account as follows: maximum and minimum values of pH, maximum and minimum values of microbial populations (Bautista-Gallego et al, 2011).…”
Section: Statistical and Explorative Multivariate Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The nucleic acids were extracted by a NucleoSpin ® tissue kit (Macherey-Nagel, Germany) according to the protocols provided by the manufacturer. DNA fragments were amplified by using primer 27 F (5ʹ-AGAGTTTGATCCTGGCTCAG-3ʹ) and primer 1492 R (5ʹ-GGTTACCTTGTTACGACTT-3ʹ) (Bautista-Gallego et al, 2013). The PCR products were purified using a PureLink TM PCR purification kit (Invitrogen, USA) according to the manufacture's protocol and the purified PCR product was sequenced using a 3130 genetic analyser (Applied Biosystems, Japan).…”
Section: Identification Of the Probiotic Strainsmentioning
confidence: 99%
“…Autoaggregation and hydrophobicity has been applied as a measurement of the ability of bacteria to adhere to cell monolayers (Bautista-Gallego et al, 2013). In same direction, a correlation between hydrophobicity and adhesion ability has been observed (Ehrmann et al, 2002), while some reports has concluded that hydrophobicity values do not correlate with adhesion properties (Ramos et al, 2013).…”
Section: Molecular Identificationmentioning
confidence: 99%